Peran Orang Tua dalam Mengembangkan Karakter Positif Anak Usia Dini - Muhammad Japar; Purwati Purwati; Rohmawan Adi Pratama; Susmawati Surya Asih (Jurnal Pemberdayaan Masyarakat, 2023)
Positive character is an attitude that is formed from environmental education either at home or at school. Children unintentionally have a positive character on the upbringing of parents and teachers. The purpose of this service is parenting as a method to broaden understanding of the role of parents in order to increase the inculcation of positive character attitudes in early childhood at Bustanul Athfal (BA) Aisyiyah Meduro. This training also aims to produce changes in early childhood behavior so that they can apply positive character traits in their surroundings. The method applied in this activity is parenting and providing training on positive character education so that parents and teachers can apply strategies and ways to instill morals in early childhood. The results of the service activities obtained are that parents can understand the needs of children so they can provide the best service by making their children a person with character. as well as being able to apply it to children to have positive personalities such as discipline, mutual help, honesty, independence, responsibility and courtesy towards others in the surrounding environment as well as students in everyday life.